In the course of justice : the selected papers and speeches of Justice Mohammed Bello, the honourable chief justice of the Federal Republic of Nigeria - Bello, Mohammed, 1930- (Lagos, Nigeria : Patrioni Books, 1995)
The selected papers and speeches of Justice Mohammed Bello, the honourable chief justice of the Federal Republic of Nigeria
Includes index.
oif 04/11/14
Loan
Keywords: Justice, Administration of -- Nigeria; Law reform -- Nigeria